Pola Asuh Otoriter, Konformitas dan Perilaku School Bullying - Tis’Ina, Nur Arofah; ., Suroso (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. The purpose of this study is to examine the correlation betweenauthoritarian parentig and conformity with school bullying on MTs X Sidoarjostudents, using quantitative method. Subjects were 65 MTs students. Researchvariables were measured using school bullying scale, authoritarian parenting scaleand conformity scale. Data were analyzed using regression analysis. The resultsshowed that authoritarian parenting and conformity significantly associated withschool bullying. Separately, authoritarian parenting significantly has a positivecorrelation with school bullying and conformity also has a positive correlation withschool bullying.Keywords: Authoritarian parenting and Conformity with School bullying